Five-year risk of stroke after TIA or minor ischemic stroke - Amarenco, Pierre; Hennerici, Michael G. (The New England journal of medicine, 2018)
Original Article from The New England Journal of Medicine — Five-Year Risk of Stroke after TIA or Minor Ischemic Stroke